Mathematical modeling of wave impacts on inclined seawall - Mohd Zuki, Salleh; Mohd Shahridwan, Ramli; Fadhlyya Arawaney, Abdul Ghani; Nor Aida Zuraimi, Md Noar; Greenhow, Martin (American Institute of Physics Inc., 2017)
This paper discusses a mathematical model of the large, short-lived pressure by waves breaking against inclined coastal structures. The theory of pressure impulse, P proposed by Cooker which simplify the highly timedependent and very nonlinear problem by considering the time integral of the pressure over the duration of the impact pressure-impulse is used in this study. P satisfies Laplace's equation and perturbation theory is applied to this model and is solved analytically using MATLAB. The correlation between the pressure impulse and the inclination angle of a wall is investigated theoretically. It is found that as angle of inclination seawall increases, the pressure impulse also increases